In Vivo Effects of Josamycin, Erythromycin, and Placebo Therapy on Nasal Carriage of Staphylococcus aureus - Wilson, Samuel Z. (1977)
Healthy nasal carriers of Staphylococcus aureus were randomly assigned to one of three treatment regimens: josamycin (1.5 g/day), erythromycin stearate (1.0 g/day), or placebo, each administered orally for 7 days. Quantitative nasal cultures were obtained from each subject at intervals before, during, and after treatment. All 25 placebo-treated subjects had positive nasal cultures for S. aureus at all culture intervals. Both josamycin and erythromycin were equally effective in reducing the carrier rates and in decreasing the total numbers of S. aureus isolated from subjects with positive cultures during treatment. No increase in in vitro antibiotic resistance was detected in isolates obtained after therapy. Both antibiotics were well tolerated, and toxicity was not encountered with either drug.